Developing the numerical sense of the first intermediate grade students using strategies mental arithmetic (Journal of the College of Basic Education, 2023)
The observer and follower of the development of school mathematics notes that the mathematics of the first centuryThe twenty-something focuses on developing thinking, its skills, and general understanding of the sports system.on mathematical structures rather than mathematical operations and procedures, and that one of the motives for developing its educationAnd learning them, as William Obaid asserts, is to get rid of the routine traditional skills and concepts.definitions and algorithms that are on the verge of falling into disrepair and that have been marginalized by computers in light of the fact that man thinksComputers are calculated and facilitated with the intention of man solving his problems and advancing his innovations.